Pemberdayaan Masyarakat melalui Program Kerja Pendidikan Desa Berkualitas di SDN I Semolowaru - Gyska Indah Harya; Pelangi Nerisa Arfina; Hilda Febrianti Sukma; Kadek Adynda Tasheya; Gadis Cantik Bunga Tunjungwangi (Jurnal Pengabdian Masyarakat Waradin, 2024)
Education is a vital and important aspect of a country's development and its ability to compete globally. The education concept emphasizes the development of students' character, critical thinking skills, social skills, and teacher skills to provide effective and engaging learning. The educational program includes Socialization and Computer Learning Techniques, Digitalization of Learning through educational videos, and EcoPrint. The program is conducted at SDN I Semolowaru, Surabaya, aiming to improve the quality of education and meet local needs. The program is conducted by 28 KKN students at the National University "Veteran" East Java, providing training and guidance. The results show that students with new perspectives are more likely to succeed, and 80% of students are able to understand all materials provided during learning. This program can support the Indonesian Education and Culture Program in educating the nation's children.